Long‐term reversal of diabetes in non‐obese diabetic mice by liver‐directed gene therapy. (25th January 2013) - Ren, Binhai; O'Brien, Bronwyn A.; Byrne, Michelle R.; Ch'ng, Edwin; Gatt, Prudence N.; Swan, M. Anne; Nassif, Najah T.; Wei, Ming Q.; Gijsbers, Rik; Debyser, Zeger; Simpson, Ann M.
Abstract Background Type 1 diabetes (T1D) results from an autoimmune attack against the insulin‐producing β‐cells of the pancreas. The present study aimed to reverse T1D by gene therapy. Methods We used a novel surgical technique, which involves isolating the liver from the circulation before the delivery of a lentiviral vector carrying furin‐cleavable human insulin (INS‐FUR) or empty vector to the livers of diabetic non‐obese diabetic mice (NOD). This was compared with the direct injection of the vector into the portal circulation. Mice were monitored for body weight and blood glucose. Intravenous glucose tolerance tests were performed. Expression of insulin and pancreatic transcription factors was determined by the reverse transcriptase‐polymerase chain reaction and immunohistochemistry and immunoelectron microscopy was used to localise insulin. Results Using the novel surgical technique, we achieved long‐term transduction (42% efficiency) of hepatocytes, restored normoglycaemia for 150 days (experimental endpoint) and re‐established normal glucose tolerance. We showed the expression of β‐cell transcription factors, murine insulin, glucagon and somatostatin, and hepatic storage of insulin in granules. The expression of hepatic markers, C/EBP‐β, G6PC, AAT and GLUI was down‐regulated in INS‐FUR‐treated livers. Liver function tests remained normal, with no evidence of intrahepatic inflammation or autoimmune destruction of the insulin‐secreting liver tissue. By comparison, direct injection of INS‐FUR reduced blood glucose levels, and no pancreatic transdifferentiation or normal glucose tolerance was observed. Conclusions This gene therapy protocol has, for the first time, permanently reversed T1D with normal glucose tolerance in NOD mice and, as such, represents a novel therapeutic strategy for the treatment of T1D. Copyright © 2013 John Wiley & Sons, Ltd.